Effect of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Operating Expenses to Operating Income (BOPO) on Liquidity as Measured by Loan to Deposit Ratio at Standard Chartered Bank Indonesia - Hablil Ikhwana (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2020)
The purpose of this research is to analyze and test the effect of CAR, NPL, BOPO on Standard Chartered Bank Indonesia's LDR. This type of research is explanatory research. The sample used in this study is Standard Chartered Bank Indonesia, which published its financial statements for the period 2006-2013. Data collection techniques are library research and field research. This study used descriptive analysis, classical assumption test and multiple linear regression for data analysis with the help of the Eviews 6 program. From the analysis test results it is known that the CAR, BOPO and NPL ratios did not affect the LDR ratio during the 2006-2013 period.